ANALISIS PERBANDINGAN METODE DETEKSI TEPI ROBERT, PREWITT, DAN CANNY UNTUK PENDETEKSIAN TEPI TULISAN AKSARA BALI - Ida Bagus Adisimakrisna Peling; Made Pasek Agus Ariawan; Gde Brahupadhya Subiksa; I Gede Angga Saputra (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Edge detection is an important analysis in digital image processing. An edge in an image is a border between two different objects or structures, and this edge information can provide important insight into the structure of objects in the image. The edge detection process aims to find the location of significant changes in intensity, which often reflect object boundaries or prominent features. Edge detection techniques have several methods such as Robert, Prewitt and Canny, where each method will produce a different processed image. In this paper, a comparison is made of the use of edge detection methods to process images of written Balinese script, which often have various different patterns in each writing, so that edge detection is expected to produce a clear image of written Balinese script using these three edge detection methods. as a comparison. It is hoped that the results of this research will provide valuable insight in selecting the optimal edge detection method for image processing of Balinese script.